RI 4561 Investigation Of The Dayton Iron Deposit Lyon And Storey Counties, Nev. - Robert W. Geehan (The National Institute for Occupational Safety and Health (NIOSH), 1949)
A preliminary examination of the Dayton iron deposit was made in 1941 and 1942 by Paul E. Pesonen and O. H. Metzger, engineers of the Bureau of Nines. Trenching and sampling were recommended, to be followed by core drilling if favorable results were obtained. The Bureau of Mines conducted a project at the property from June to December 1942. The deposit is in sec. 6, T. 17 N., R. 23 E.; sec. 31, T. 18 N., R. 23 E.; sec. 36, T. 18 N., R. 22 E.; and sec. 1, T. 17 N., R. 22 E., M. D. B. & M., about 15 miles west of Lahontan Reservoir in Lyon and Storey Counties, Nev. It lies at an altitude of about 4,500 feet north of the Carson Plains, in the foothill section of mountains that rise to about 7,000 feet to the north of the property. The deposit may be reached by driving 12.5 miles northeast of Dayton over U. S. Highway 50, thence northerly 2.7 miles over a dirt road to the property. The climate is hot and dry in summer, with occasional thunderstorms some of cloudburst variety, and frequent high winds. Winters are usually moderate, with light snowfall and some subfreezing temperature.